计算(2x+y+1)(2x+y-1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 02:39:13
计算(2x+y+1)(2x+y-1)计算(2x+y+1)(2x+y-1)计算(2x+y+1)(2x+y-1)(2x+y+1)(2x+y-1)=[(2x+y)+1][(2x+y)-1]=(2x+y)^2
计算(2x+y+1)(2x+y-1)
计算(2x+y+1)(2x+y-1)
计算(2x+y+1)(2x+y-1)
(2x+y+1)(2x+y-1)
=[(2x+y)+1][(2x+y)-1]
=(2x+y)^2-1
=4x^2+4xy+y^2-1
(2x+y+1)(2x+y-1)
=(2x+y)^2-1
=4x^2+4xy+y^2-1
把2x+y看做整体
然后就是(2x+y)的平方-1
答案就是4x的平方+4xy+y的平方-1
(2x+y+1)(2x+y-1)=(2x+y)^2-1=4x^2+y^2+4xy-1
计算(x+y-1)^2
(x+y)(x-y)-(2x+y)(x-y+1)计算要过程
计算:2/x+1/(x-y)
计算:1/2x-1/x+y×(x+y/2x-x-y)
计算:1/(2x) - 1/(x+y)((x+y)/(2x) - x - y)
1/(2x) - 1/(x+y)*((x+y)/(2x)-x-y) 计算.
计算2x/1-x+y/1·(2x/x+y-x-y)
计算:(4xy(x-y)^-1+(x(y^-1)-(x^-1)y)/((x^-1)+(y^-1)))*(x+y)^-2
计算:1/x^2-y^2+2/(x-y)^2
计算:1/(x-y)+1/(2y-2x)
计算(2x+y+1)(2x+y-1)
计算:1(y-x)+1/(2y-2x)
x^-2-y-2分之x^-1-y^-1计算
计算(2x-y+1)(2x+y-1)
计算(x-2y+1)(x+2y+1)
计算(X+2Y-1)(X+2Y+1)
计算:5x-2y-6+ (1/x) + (1/y)
计算-1/9(x+y)^2+(x-y)^2